School-to-Work transition in Peru: an assessment of search time, job duration and skill mismatch on youth labor market integration. - Mendoza Sánchez, José Antonio; Daga Acevedo, Mirko David (Pontificia Universidad Católica del Perú. Dirección de Gestión de la Investigación., 2018)
Nowadays, young workers around the world are facing a paradox: they are better educated but worst employed. This situation is no very different either in Latin America or Peru, where unemployment and underemployment rates reach high levels among young workers. This work reviews some theories trying to explain this phenomena. From this literature review, three variables were selected as appropriated for assessing young labor market in Peru: job searching time, first job duration and skill mismatch. Applying the nested Tobit model proposed by Lee(1992), we found : first, the more educated is a person the less time has to devote to job searching. Second, skill mismatch likelihood increases until the undergraduate level, reducing when persons reach postgraduate level. Further, search time also increases skill mismatch likelihood. Third, regarding job duration, only under and after graduate level reduces the time in fist employment. Also, the longer is the time search, the shorter is the job duration. This results show that a wider debate regarding youth’s employment is required, as well as further studies addressing these phenomena. Furthermore, results suggests universities are not meeting labor markets requirements. This could be or not a problem, depending upon universities are considered as research centers or as a labor force providers. Again, this should be part of a debate and a future research agenda.
Keywords: Youth Labor; Market Integration; Work Transition; http://purl.org/pe-repo/ocde/ford#5.09.01